A Prospective, Randomized, Open-Label Study Comparing Recovery Characteristics between Desflurane and Sevoflurane Anesthesia in Elderly Patients Undergoing Elective Supratentorial Craniotomy - Sailaja, Mallampalli. N.; Lakshminarasimhaiah, Geetha; Srinivas, Rakshith (Journal of Neuroanaesthesiology and Critical Care, 2023)
Background Sevoflurane and desflurane are the two commonly used volatile anesthetics and it is mandatory to comprehend their hemodynamic and recovery profiles to ensure safe administration and early recovery in elderly neurosurgical patients. The primary objective of the study was to compare the recovery profiles of sevoflurane and desflurane in elderly patients undergoing supratentorial craniotomy. The secondary outcome measures studied were intraoperative hemodynamic changes, intraoperative brain condition, and early postoperative cognition using short orientation memory concentration test (SOMCT).Methods The prospective, open-labeled study involving 78 elderly patients undergoing elective supratentorial craniotomies randomized the subjects into sevoflurane and desflurane groups in the ratio of 1:1 (39 each). Pre- and early postoperative cognitive function of the patient was assessed using SOMCT. Time for emergence, extubation, and recovery were also compared between the groups. Hemodynamic parameters during surgery and brain relaxation were recorded. Student's t-test was used to find the significance of study parameters on a continuous scale and chi-squared test to find the significance of study parameters on a categorical scale between two groups.Results The mean emergence time (minutes) was found to be significantly longer in sevoflurane group as opposed to desflurane (9.44 ± 2.07 vs. 8.28 ± 2.53, p = 0.02). Similarly, the mean recovery time was significantly longer for sevoflurane group than desflurane (17.33 ± 3.36 vs. 15.64 ± 4.63, p = 0.03). A statistically significant difference in pre- and early postoperative SOMCT was observed between the two groups (5.31 ± 2.89 vs. 4.33 ± 1.74, p = 0.04) with better early postoperative SOMCT (p = 0.05) in desflurane group. However, extubation time, average duration of surgery, brain relaxation, and modified Aldrete score were comparable between the groups.Conclusion Elderly patients who received desflurane had a shorter emergence and recovery time compared with sevoflurane. Improved early postoperative SOMCT scores were noted in desflurane group.
Keywords: desflurane; sevoflurane; anesthesia; supratentorial craniotomy; elderly